Adolescent Empowerment through Simulation-Based Household Emergency Response in Rimbo Recap Village - Leli Mulyati; Fatimah Khoirini; Derison Marsinova (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Adolescents play an important role in assisting in the initial handling of emergencies. However, limited knowledge and skills in emergencies among adolescents remain a problem, especially in Rimbo Recap Village, Rejang Lebong Regency. Many adolescents do not yet have the basic knowledge and skills in handling emergencies such as fires, serious injuries, heart attacks, or other urgent medical situations. As a result, when an emergency occurs, treatment is often slow and inappropriate, which can be fatal for the victim and worsen the situation. Adolescent Knowledge and Skills are increased, at least 50% of adolescents in Rimbo Recap Village are expected to have basic knowledge and skills in handling emergencies at home, and are expected to reduce the rate of fatalities and serious injuries due to delays or errors in handling. The activity was conducted over 2 days (18-19 October 2025), with preparation, implementation, and evaluation stages. The first day focused on theory, and the second on practical activities for handling emergencies. Evaluation was conducted through pretests and posttests, participant skill observation, and follow-up monitoring, involving a total of 25 participants. There was a significant increase in adolescent knowledge after the training, with an average score increasing from 62.80 ± 11.00 in the pretest to 78.80 ± 4.10 in the posttest. The paired t-test showed a significant difference between the pretest and posttest scores (p-value 0.001). Emergency training is effective in improving adolescent knowledge and skills in handling emergencies at home. This activity has the potential to strengthen adolescents’ and village communities’ preparedness to face emergency conditions on an ongoing basis. Keywords: Emergency Nursing, Household Emergency, First Aid, Adolescents.